Effects on Turkish ice cream employees' musculoskeletal pain of a physical activity and ergonomics improvement program in the workplace - (:unkn) unknown (TAYLOR & FRANCIS LTD)
Objectives. This study aimed to investigate the effects of a physical activity and ergonomics improvement program (PAEIP) on employees' musculoskeletal pain. Methods. The sampling group included 120 employees who met the criteria and were randomly assigned to the intervention group (n = 57) and the control group (n = 63). The visual analog scale, the Nordic musculoskeletal survey and rapid upper limb assessment (RULA) were used for collecting data. Results. When pre-test and post-test pain scores of the intervention group were compared, the average post-test scores were significantly lower in the neck, shoulder, wrist and lower back regions than the pre-test scores. When the intervention and control group RULA scores were compared, in the intervention group the proportion of employees found in an 'acceptable posture' level was 0% in the pre-test and 5.3% in the post-test, and in the same group the proportion of employees in the 'further investigation and change may be needed' level was 31.6% in the pre-test and increased to 61.4% in the post-test. Conclusion. As a result, the PAEIP has been found effective in reducing the ergonomic risks associated with upper extremities and rate or intensity of musculoskeletal pain.
Keywords: Neck pain; hand; wrist pain; foot pain; RISK-FACTORS; LOWER BACK; SYMPTOMS; WORKERS; PREVALENCE; DISORDERS; POSTURE; NECK